TINA EVANS’S DEPRESSION IN DEAN KOONTZ’S THE EYES OF DARKNESS - Sulistiyo Rahmawati, Yuni; Wahyono, Danu (TANDA, 2022)
This study analyzes the depression experienced by Tina Evans in the novel of The Eyes of Darkness written by Dean Koontz. The focus of this research is the symptoms of depression, the causes, and effects of depression, as well as the solution of the depression of Tina Evans. This study uses a qualitative research and applies a psychological approach. From this analysis, it can be found that there are two symptoms of depression experienced by Tina Evans: sadness and sleep disturbances. Meanwhile the cause of Tina's depression is the stress of losing someone she loves. She gets divorce as her husband, Michael Evans, has an affair. Trauma becomes her next cause of her depression, and the last cause is the spiritual terror. Her depression provides three effects: insomnia, lack of concentration, and nightmares. In overcoming her depression she manages it in various ways. There are six solutions in overcoming her depression. The first is to distract her mind by hard working. The next is to take significant responsibility for her work. The third is trying to divert her mind by consuming alcohol. The fourth is to think positively. The fifth is expressing herself to talk to other people, in this case, to her boyfriend. The last one is to accept the spiritual terror haunting her and find the facts about the death of her son Danny Evans with the help of Elliot Stryker.